2016
DOI: 10.1021/acsami.5b11949
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Titanium Substrates with Chimeric Peptides Comprising Antimicrobial and Titanium-Binding Motifs Connected by Linkers To Inhibit Biofilm Formation

Abstract: Bacterial adhesion and biofilm formation are the primary causes of implant-associated infection, which is difficult to eliminate and may induce failure in dental implants. Chimeric peptides with both binding and antimicrobial motifs may provide a promising alternative to inhibit biofilm formation on titanium surfaces. In this study, chimeric peptides were designed by connecting an antimicrobial motif (JH8194: KRLFRRWQWRMKKY) with a binding motif (minTBP-1: RKLPDA) directly or via flexible/rigid linkers to modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 59 publications
0
78
0
Order By: Relevance
“…For example, the hst-5 derivative, JH8194, is a promising candidate to act as a surface substrate in dental implants to prevent peri-implantitis and peri-implant mucositis whilst decreasing infections [259,260]. A major focus in the medical development of histatins has been in the preparation of formulations to treat oral diseases and infections [141].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%
“…For example, the hst-5 derivative, JH8194, is a promising candidate to act as a surface substrate in dental implants to prevent peri-implantitis and peri-implant mucositis whilst decreasing infections [259,260]. A major focus in the medical development of histatins has been in the preparation of formulations to treat oral diseases and infections [141].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%
“…Another more recent study confirmed the antibiofilm activity of min-TBP on other types of biofilm formation ( S . gordonii , Streptococcus sanguis , S. mutans , Staphylococcus epidermidis , and so on) on Ti implants [102104]. …”
Section: Antibiofilm Peptide Applications In Periodonticsmentioning
confidence: 99%
“…Anchoring the peptides to the resin minimizes the interactions between peptides. Several studies including ours have shown that spacer domains provides flexibility for peptides to keep their active conformation while they interact with the surfaces, which improves their biological function [43,54,93]. For example, a rigid spacer was shown to improve the antibacterial activity of a peptide compared to a flexible spacer of the same length [43].…”
Section: Bacterial Viability On Treated Discsmentioning
confidence: 92%